2000
DOI: 10.1023/a:1002866911650
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Systemic administration of beta-casein heptapeptide beta-casomorphin-7 (YPFPGPI, 1 mg/kg daily) to 10-23-day-old albino rat pups produced delayed anxiolytic effects, which were more pronounced in female than in male rats. Experimental findings confirm our assumption on the important role of nutritional opioids in brain development in newborn mammals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Previous observations showed that newborn child receives 20-25 mg exogenous opioids with 2 mg dietary casein [1]. Our study provides experimental support to the potential role of food components in vital activity of the organism.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Previous observations showed that newborn child receives 20-25 mg exogenous opioids with 2 mg dietary casein [1]. Our study provides experimental support to the potential role of food components in vital activity of the organism.…”
Section: Resultssupporting
confidence: 77%
“…The dose of this peptide (1 mg/kg) is comparable with the amount of dietary β-casomorphin, which enters the mammalian organism during early postnatal ontogeny [1,12]. The rats were subjected to single (day 4 of life) or 5-fold treatment with test peptide (days 2-6 of life).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was confirmed by numerous recent experimental data on delayed effects of administration of some pharmacological agents to rat and mouse pups [3][4][5].…”
mentioning
confidence: 63%
“…It has been shown that they influence nociception [1,2], regulate maternal and infant behavior [3], and possess anxiolytic [4] and cardiotropic actions [5]. However, the mechanisms through which these peptide bioregulators affect different physiological functions are still unclear.…”
Section: Introductionmentioning
confidence: 99%